Pilot study on the evaluation of the effectiveness of psychocorrection methods that include EEG-training and VR headset in athletes involved in extreme kinds of sports - V. I. Pustovoit; S. E. Nazaryan; E. Ya. Adoeva; M. S. Klyuchnikov; N. A. Kirichenco; A. S. Samoilov (National Electronic Information Consortium (NEICON), 2021)
Objective: to evaluate the effectiveness of psychocorrection based on the methods of selfregulation in athletes.Materials and methods: the effectiveness was evaluated on 104 male athletes who had an optimal level of psychoemotional state of the body during a background examination by electroencephalography (EEG). The subjects were randomly assigned to three groups of psychocorrection: control, EEGtraining, and VRtherapy. Mathematical and statistical processing was carried out in Statistica 7.Results: the average values of the wave intensity index (WII) after psychological correction using the following methods: EEGtraining and VRtherapy showed positive EEG dynamics in athletes of the second group (EEGtraining) 65,6 % (21) and the third group (Vrtherapy) 73,8 % (31) of the subjects, respectively. Whereas in the control group, selfhealing was recorded in 9 (30 %) athletes without psychocorrection procedures.Conclusion: the quantitative criterion of WII is a universal informative indicator of the functional activity of the brain for evaluating the effectiveness of psychocorrection aimed at optimizing the psychoemotional state. Psychocorrection of athletes using EEGtraining and VRtherapy provides efficiency in 73.8 and 65.6 % of cases, which significantly softens prestart tension as a result of reducing anxiety and restoring the psychoemotional state of the body to an optimal level by involving the psychological reserve.